2023
DOI: 10.3390/ijms241814126
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic Ovary Syndrome and Oxidative Stress—From Bench to Bedside

Natalia Zeber-Lubecka,
Michał Ciebiera,
Ewa E. Hennig

Abstract: Oxidative stress (OS) is a condition that occurs as a result of an imbalance between the production of reactive oxygen species (ROS) and the body’s ability to detoxify and neutralize them. It can play a role in a variety of reproductive system conditions, including polycystic ovary syndrome (PCOS), endometriosis, preeclampsia, and infertility. In this review, we briefly discuss the links between oxidative stress and PCOS. Mitochondrial mutations may lead to impaired oxidative phosphorylation (OXPHOS), decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 139 publications
0
4
0
Order By: Relevance
“…In a previous study, Zeber-Lubecka et al summarized that any defects at the level of mtDNA replication affect the formation of numerous mutations; thus, mtDNA damage can be a contributor in the pathogenesis of PCOS. They demonstrated that mitochondrial mutations can lead to impaired oxidative phosphorylation, disruption to insulin signaling pathways, and result in an increased ROS production and a consequent oocyte impairment [ 67 ]. Sang-Hea Lee et al have demonstrated that the number of mtDNA copies were found to be lower in women with PCOS than in the control groups [ 68 ], with a negative correlation with the severity of the syndrome.…”
Section: Role Of Oxidative Stress and Inflammation In Pcosmentioning
confidence: 99%
“…In a previous study, Zeber-Lubecka et al summarized that any defects at the level of mtDNA replication affect the formation of numerous mutations; thus, mtDNA damage can be a contributor in the pathogenesis of PCOS. They demonstrated that mitochondrial mutations can lead to impaired oxidative phosphorylation, disruption to insulin signaling pathways, and result in an increased ROS production and a consequent oocyte impairment [ 67 ]. Sang-Hea Lee et al have demonstrated that the number of mtDNA copies were found to be lower in women with PCOS than in the control groups [ 68 ], with a negative correlation with the severity of the syndrome.…”
Section: Role Of Oxidative Stress and Inflammation In Pcosmentioning
confidence: 99%
“…Antioxidants, notably catalase, can alleviate oxidative stress and inflammation in these conditions, potentially improving fertility and pregnancy outcomes [ 153 ]. While research on catalase in reproductive health is still evolving, its role in combating oxidative stress suggests potential benefits in maintaining fertility and supporting healthy pregnancies.…”
Section: Role Of Catalase In Different Diseasesmentioning
confidence: 99%
“…The characteristic morphological features of polycystic ovaries are the accumulation of antral follicles of 5–8 mm and follicular growth failure ( Franks et al , 2000 , 2008 ). Its pathophysiology has not been well characterized, but various mechanisms, including endoplasmic reticulum (ER) stress ( Harada, 2022 ; Koike et al , 2023 ), oxidative stress ( Zeber-Lubecka et al , 2023 ), and abnormal inflammation and immunity ( Lima et al , 2018 ) have been implicated. Women with PCOS have high serum concentrations of pro-inflammatory molecules, such as tumor necrosis factor (TNF)-α, interleukin (IL)-1, IL-6, and IL-18 ( Kaya et al , 2010 ; Alissa et al , 2021 ; Mazloomi et al , 2023 ).…”
Section: Introductionmentioning
confidence: 99%